Design and Concept of the SMITH Phenotyping Pipeline. - Meineke, F. A.; Staubert, S.; Lobe, M.; Uciteli, A.; Loffler, M. (Stud Health Technol Inform, 2019)
Phenotyping means the determination of clinical relevant phenotypes, e.g. by classification or calculation based on EHR data. Within the German Medical Informatics Initiative, the SMITH consortium is working on the implementation of a phenotyping pipeline. to extract, structure and normalize information from the EHR data of the hospital information systems of the participating sites; to automatically apply complex algorithms and models and to enrich the data within the research data warehouses of the distributed data integration centers with the computed results. Here we present the overall picture and essential building blocks and workflows of this concept.
Keywords: Algorithms; *Electronic Health Records; *Medical Informatics; Phenotype